The Peculiar Naophorous Statuette of a Heliopolitan Priest - Klotz, David (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
First publication of a naophorous statuette from the Museum August Kestner, Hannover. This object belongs to the Heliopolitan priest Psamtek, apparently the son of the well-known vizier Psamtek-Seneb, and thus likely dates to the Thirtieth Dynasty. The statue owner’s titles provide further evidence for lesser known cults of Heliopolis, and the autobiographical inscription is unique for its concentration of unconventional enigmatic orthographies.